Monodisperse Generation of Fragrance-Loaded Microcapsules with Hydrophilic Polymer Shells Using Microfluidic Devices - Hirotada Hirama; Hiromasa Miyauchi; Yuki Matsuo; Masanori Hayase (Applied Sciences)
Fragrance is an odorous, volatile substance. Conventionally, encapsulation is performed to improve the preservation and persistence of smells. Typical methods of fragrance encapsulation include interfacial polymerization and the sol-gel method. However, there are issues such as low encapsulation efficiency and difficulty in controlling capsule size and shell thickness. Recently, a method for generating water-in-oil-water (W/O/W)-type microcapsules using microfluidic technology was reported. This made it possible to achieve high encapsulation efficiency and excellent control of the capsule diameter and shell dimensions. However, because this method involves a preliminary dispersion process for fragrance, the production process is more complicated than that of microcapsules using general microfluidic technology. In this study, we used a method for generating oil-in-water-in-oil (O/W/O)-type microcapsules in a microchannel with partially controlled wettability and achieved the generation of monodisperse fragrance-containing microcapsules with a hydrophilic polymer shell without the need for a preliminary dispersion process.